PENGARUH STRES AKADEMIK TERHADAP PERILAKU MEROKOK PADA MAHASISWA - Muhammad Wildan Afif; Muhimmatul Hasanah; Ima Fitri Sholichah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Academic stress is something that happens in the world of education, the impact of academic stress in the form of positive and negative impacts. Positive impacts such as self-development, negative impacts such as smoking. This study aims to determine the effect of academic stress on smoking behavior in students. The research method uses a quantitative approach. The population of all active students at the University of Muhammadiyah Gresik Batch 2018 are male, using a purposive sampling technique that collects 58 active, active students. The measuring instrument of this research is the Student Life Stress Inventory (SLSI) scale developed by Gadzella (1991) and the smoking behavior scale developed by Leventhal & Cleary (1980). Test the validity of the scale using content validity. Reliability test using Alpha Cronbach. The data analysis technique used simple regression analysis with a value of sig .000 <0.05, which means that there is an influence between academic stress and smoking behavior in students.